CuI‐catalyzed tandem synthesis of thioethers using aryl halides, electron‐deficient alkenes, and sodium iso‐propyl xanthogenate. (3rd February 2020) - Abbasi, Mohammad; Nowrouzi, Najmeh; Khezri, Rahimeh
Abstract : A ligand‐free, CuI‐catalyzed protocol was developed for the one‐step preparation of Michael adducts of aromatic thiols in high yields by reacting a mixture of an aryl halide and an electron‐deficient alkene with sodium iso ‐propyl xanthogenate. Abstract : Synthesis of thioethers by a one‐pot, tandem reaction of aryl halides, sodium iso ‐propyl xanthogenate, and electron‐deficient alkenes.